Synopses and Lists Textual Practices in the Pre-Modern World - Bernheimer, Teresa; Vollandt, Ronny (Semitic Languages and Cultures, 2023)
Textual practices in pre-modern societies cover a great range of representations, from the literary to the pictorial. Among the most intriguing are synopses and lists. While lists provide a complete enumeration of ideas, people, events, or terms, synopses juxtapose one against the other. To understand how they were planned, produced, and consumed, is to gain insight into the practices of what one can call management of knowledge in a time before our own. The present volume is the product of two workshops held in 2019 and 2021 as part of the research focus Textual Practices in the Pre-Modern World: Texts and Ideas between Aksum, Constantinople, and Baghdad, which was generously supported and funded by the Centre for Advanced Study (CAS) at Ludwig-Maximilians-Universität (LMU), Munich. Aiming to understand how synopses and lists function in the literatures of the great intellectual traditions of late antiquity-the ancient Near East, ancient philosophy, and the three monotheistic religions Judaism, Christianity, and Islam-the volume offers a historical and transcultural perspective on synopses and lists, highlighting the centrality of these textual practices to allow storing, retrieving, selecting, and organising this knowledge. Both make deliberate - yet not always explicit - choices as to what is included and excluded, thereby creating lasting hierarchies and canons.